POLYPHENOL PROFILING IN THE LEAVES OF PLANTS FROM THE CATCHMENT AREA OF RIVER BEAS, INDIA - V. KUMAR; A. SHARMA; R. BHARDWAJ; ASHWANI KUMAR THUKRAL (International Journal of Pharma and Bio Sciences, 2015)
A total of 11 polyphenols viz. gallic acid, catechin, chlorogenic acid, epicatechin, caffeic acid, umbelliferone, coumaric acid, rutin, quercetin, kaempferol and ellagic acid were analyzed in the leaves of 16 plants by using UHPLC (Ultra high performance liquid chromatography). Polygonum barbatum (1756.42 µg/g dw) had the highest, whereas Cannabis sativa (18.01 µg/g dw) had the lowest content of polyphenols. Highest positive Pearson’s correlation was found between the umbelliferone and kaempferol. Cluster analysis revealed that all the members of family asteraceae and chenopodiaceae were included in the same cluster and had close proximity on the basis of polyphenol content. The total variance of 65.89% was explained by first three components of PCA (principal component analysis). In factor analysis factor-1, factor-2 and factor-3 accounted 25.3%, 24.4% and 16.2% of the total variance respectively.